Seasonal changes in berry fluorescence induced by different levels of uv-radiation - Lopes, C.M. (2022)
Plant stress is usually diagnosed via physiological measurements on leaves such as water potential, photosynthetic rate or chlorophyll fluorescence. Since stress in the case of grapevines is of concern with respect to the quality of the fruit, we attempted to use one of the above mentioned techniques, chlorophyll fluorescence, directly on the fruit itself in order to investigate stress responses in vivo. Berry fluorescence was measured in an experiment with different levels of UV-B and UV-A radiation in the field in 2000 in Geisenheim with the variety Riesling. UV radiation has been shown to affect chlorophyll and was thus likely to show differences in fluorescence signals. Berry fluorescence was measured periodically between veraison and harvest on darkadapted berries (20min). For each berry, a light response curve was recorded followed by a recovery phase in the dark. The maximum quantum yield of PSII (qY) was determined after a saturation pulse at each light intensity. The qY decreased exponentially with increasing light intensity. The response level of the quantum yield of PSII decreased during ripening indicating a loss in chlorophyll and/or PSII capacity for all treatments. Effects of the different levels of UV-radiation on the light curve were only detected at the end of the ripening period, with higher quantum yield values recorded for the treatments protected against UV-A and UV-A+UV-B. Similar results were obtained after recovery in the dark. Changes in fluorescence signals were accompanied by a visual change in berry colour indicating changes in skin pigmentation, which may also have some effect on fruit quality